Ion channels in health and disease - Pitt, Geoffrey S.; ScienceDirect eBooks (London, UK : Academic Press is an imprint of Elsevier, 2016)
Ion Channels in Health and Disease provides key insight to allow researchers to generate discoveries across disease states. A single resource that integrates disparate areas of biology and disease ion channel biology, this publication includes cross-referencing for disease, channels, and tissues. Offers a broad view of research of interest to early and experienced researchers across biological and biomedical research.
GENETIC AND PHARMACOLOGICAL TREATMENT OF DRAVET SYNDROMEGENETIC BACKGROUND EFFECTS IN DRAVET SYNDROME; GENETIC DISSECTION OF PHENOTYPES IN DRAVET SYNDROME; DRAVET SYNDROME AS A SODIUM CHANNEL INTERNEURONOPATHY; CONTRASTING VIEWS FROM STUDIES OF HUMAN-INDUCED PLURIPOTENT STEM CELLS; References; 5 -- Diagnosis, Treatment, and Mechanisms of Long QT Syndrome ; INTRODUCTION; DIAGNOSIS OF LONG QT SYNDROME; CLINICAL COURSE; GENES RESPONSIBLE FOR LONG QT SYNDROME (SEE TABLE 5.1); KCNQ1 (KV7.1, KVLQT1) (LQT1); KCNH2 (KV11.1, hERG) (LQT2); SCN5A (NaV1.5) (LQT3); ANK2 (LQT4); KCNE1 (LQT5); KCNE2 (LQT6)
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed July 20, 2016).
Includes bibliographical references and index.
Elsevier
Keywords: Ion channels; Ion channels; SCIENCE / Life Sciences / Anatomy & Physiology; Ion Channels; Electronic books